Pengaruh Pengadaan dan Penganggaran serta Pendistribusian terhadap Ketersediaan Obat di Instalasi Farmasi Dinas Kesehatan Kabupaten Manokwari Papua Barat - Yuliarti Pasau; Kosasih Kosasih; Ayu Laili Rahmiyati; Vip Paramarta; Taufan Nugroho (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of procurement and budgeting and distribution on drug availability at the Pharmacy Installation of the Manokwari Regency Health Office, West Papua Province. The research method used is a quantitative approach. The data analysis used is descriptive analysis and verification analysis using multiple regression analysis. Descriptive methods focus on describing and analyzing the results of research and verification methods are used to test the relationship between variables. The sample consisted of 77 employees who were taken using saturated sampling technique. The results of descriptive analysis show that in the variables of procurement, budgeting, and distribution of drugs are in the category of enough towards good and good towards very good, there are still some shortcomings that must be considered for improvement. Statistically, the results of verification tests with multiple regression analysis models show that the drug procurement variable has a significant effect on drug availability with a coefficient value of 0.409 and a p-value of 0.000. Drug budgeting also has a significant effect with a coefficient value of 0.021 and a p-value of 0.003. Distribution showed a significant effect on drug availability with a coefficient value of 0.794 and a p-value of 0.000. The results of this study indicate that improvements in these three aspects can significantly increase the availability of drugs in the Pharmaceutical Installation.